Equus mitochondrial pangenome reveals independent domestication imprints in donkeys and horses - Wenchao Du; Qifan Sun; Sheng Hu; Pei Yu; Shenglong Kan; Wei Zhang (Scientific Reports)
Abstract Mitochondria are semi-autonomous organelles that play a crucial role in the energy budget of animal cells and are closely related to the locomotor abilities of animals. Equidae is renowned for including two domesticated species with distinct purposes: the endurance-oriented donkey and the power-driven horse, making it an ideal system for studying the relationship between mitochondria and locomotor abilities. In this study, to cover the genetic diversity of donkeys, we sequenced and assembled six new mitochondrial genomes from China. Meanwhile, we downloaded the published mitochondrial genomes of all species within Equus and conducted a comprehensive pan-mitochondrial genome analysis. We found that the mitochondrial genomes of Equus are highly conserved, each encoding 37 genes, including 13 protein-coding genes (PCGs). Phylogenetic analysis based on mitochondrial genomes supports previous research, indicating that the extant species in Equus are divided into three main branches: horses, donkeys, and zebras. Specifically, 761 genetic variants were identified between donkeys and horses, 68 of which were non-synonymous mutations in PCGs, potentially linked to their different locomotor abilities. Structural protein modeling indicated that despite genetic differences, the overall protein structures between donkeys and horses remain similar. This study revealed the mitochondrial genome variation patterns of domesticated animals, offering novelty perspectives on domestication imprints. Additionally, it provides reliable candidate molecular markers for the identification of donkeys and horses.